1980
DOI: 10.2337/diacare.3.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Lipoprotein Lipids to Mild Fasting Hyperglycemia and Diabetes in Pregnancy

Abstract: The available data have been examined to determine if plasma lipids or lipoproteins are altered in pregnant subjects with adult-onset (type II) diabetes, gestational diabetes, or the hyperglycemic extreme of a randomly selected group of pregnant women attending a prepaid health plan. In each of these groups, a trend is observed toward an increase in total plasma and very low density lipoprotein triglycerides and a decrease in high density lipoprotein (HDL) cholesterol. These observations indicate that measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 3 publications
5
22
0
2
Order By: Relevance
“…The high levels of total cholesterol and triglycerides in GDM patients were observed previously (Meyers-Seifer and Vohr, 1996;Grundy et al, 2006;American Diabetes Association, 2010;Marcinkevage and Narayan, 2011) and are consistent with frequent association of GDM with lipid profile modifications (Knopp et al, 1980). The significantly higher levels of HDL cholesterol observed in GDM patients compared to controls was not observed in other studies (Grundy et al, 2006;American Diabetes Association, 2010;Marcinkevage and Narayan, 2011) that reported low HDL cholesterol levels in GDM patients of different populations.…”
Section: Discussionsupporting
confidence: 86%
“…The high levels of total cholesterol and triglycerides in GDM patients were observed previously (Meyers-Seifer and Vohr, 1996;Grundy et al, 2006;American Diabetes Association, 2010;Marcinkevage and Narayan, 2011) and are consistent with frequent association of GDM with lipid profile modifications (Knopp et al, 1980). The significantly higher levels of HDL cholesterol observed in GDM patients compared to controls was not observed in other studies (Grundy et al, 2006;American Diabetes Association, 2010;Marcinkevage and Narayan, 2011) that reported low HDL cholesterol levels in GDM patients of different populations.…”
Section: Discussionsupporting
confidence: 86%
“…Knopp and colleagues studied 22 wo men with GDM and 38 controls in the third trimester of pre gnancy (35). These authors found increased pla sma concentrations of triglycerides and VLDL-cho le sterol but no difference in plasma cholesterol concen tra tions in women with GDM (35). Montelo n go and collea gues in their study also reported no differences in total cholesterol and tri gly ceride between women with GDM and controls in their first, second or third tri mester (36).…”
Section: Discussionmentioning
confidence: 94%
“…The dysli pidaemia profile observed in our study is not in accordance with reports from some other investi ga tions. Knopp and colleagues studied 22 wo men with GDM and 38 controls in the third trimester of pre gnancy (35). These authors found increased pla sma concentrations of triglycerides and VLDL-cho le sterol but no difference in plasma cholesterol concen tra tions in women with GDM (35).…”
Section: Discussionmentioning
confidence: 99%
“…They found increased plasma triglycerides and VLDL, but no difference in plasma cholesterol concentrations. 41 Zeynep Ersanli et al also found elevated Triglycerides in GDM group 10 . More recently Montelogo et al did not find any differences in serum lipid, lipoprotein or apolipoprotein concentrations in pregnant women with or without GDM 37 .…”
Section: Discussionmentioning
confidence: 99%